The handbook of international trade and finance the complete guide for international sales, finance, shipping and administration - Grath, Anders 1943- (Kogan Page, 2016)
For anyone involved in international sales, finance, shipping and administration, or for those studying for academic or professional qualifications in international trade, The Handbook of International Trade and Finance offers an extensive and topical explanation of the key finance areas. This essential reference resource provides the information necessary to help you to reduce risks and improve cash flow, identify the most competitive finance alternatives, structure the best payment terms, and minimize finance and transaction costs. This fully revised and updated 4th edition of The Handbook of International Trade and Finance also describes the negotiating process from the perspectives of both the buyer and the seller, providing valuable insight into the complete financing process, and covering key topics such as: trade risks and risk assessment; structured trade finance; methods and terms of payment; currency risk management and bonds, guarantees and standby letters of credit. The Handbook of International Trade and Finance provides a complete and thorough assessment of all the issues involved in constructing, financing and completing a cross-border transaction, as an indispensable guide for anyone dealing with international trade. The new edition also includes a section on risk management, which plays an increasingly important role in international trade from currency fluctuations to political risk and natural disasters.